PERAN AIR REBUSAN DAUN SALAM (SYZGIUM POLYANTHUM) DALAM MENURUNKAN KADAR ASAM URAT - Darussalam, Miftafu; Kartika Rukmi, Dwi (MEDIA ILMU KESEHATAN, 2016)
Background: Uric acid is a final product or a waste that is resulted from the metabolism of purines. A high level of uric acid (hyperuricemia) will cause several health problems, such as vascular inflammation, smooth muscle proliferation, and vascular lesion in kidneys. The syzygium polyanthum leaves contain bioactive substances that may affect the level of uric acid in blood. Objective: This study aimed to determine the influence of boiled water of syzygium polyanthum leaves to the changes of uric acid levels in the target area of Puskesmas Pandak 1 Bantul. Methods: This study employed pre- and post-test without control group design. The population consisted of all patients with hyperuricemia in the target area of Puskesmas Pandak 1 Bantul. Sample was selected with a concecutive sampling, gaining a total number of 24 respondents. Data were analyzed with the Wilcoxon test. The dose of boiled water of syzygium polyanthum leaves intake was 0.36g/ KgBW, once a day for 14 days. Result: This research showed that the boiled water of syzygium polyanthum leaves decreased hyperuricemia (uric acid levels), along with the significancy value of 0.009 (p <0.05). At the pre-test time, the average level of uric acid reached 7.279 mg/dl, and after the treatment, it decreased to 6.76 mg/dl. Conclusion: This study has established evidence that the boiled water of syzygium polyanthum leaves is able to decrease hyperuricemia (uric acid level in blood). Keywords: Syzygium polyanthum, boiled water of syzygium polyanthum leaves, hyperuricemia